2023
DOI: 10.3390/children10030549
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors in Ecuadorian Adolescent Survivors of Suicide

Abstract: Suicide is one of the main causes of death among the adolescent population, which is why it is considered an important mental-health problem. In addition to this situation, for each suicide, the group of people who survive it (known as suicide survivors) can present serious emotional affectations, becoming a population at risk for this problem. The purpose of this study was to analyze the effect of suicide-survivor status on risk factors and protective factors for suicide. A total of 440 adolescents with a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Another aspect that was explored to better characterize the participants was the family and social history of suicide, identifying that 16.60% of adolescents were suicide survivors, a figure slightly lower than that found in studies with Ecuadorian adolescents, where the percentage was 17.60% [37]. These data show that the risk characteristics present in the adolescents surveyed are similar to the characteristics of other populations and therefore it is expected that the results referring to the impulse to self-injurious behavior and its evaluation will not be affected by these conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another aspect that was explored to better characterize the participants was the family and social history of suicide, identifying that 16.60% of adolescents were suicide survivors, a figure slightly lower than that found in studies with Ecuadorian adolescents, where the percentage was 17.60% [37]. These data show that the risk characteristics present in the adolescents surveyed are similar to the characteristics of other populations and therefore it is expected that the results referring to the impulse to self-injurious behavior and its evaluation will not be affected by these conditions.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, these results on correlations between suicidal potential and NSSI can be confusing if we take into account that a primary factor in NSSI is non-suicidality; however, recent studies on suicide risk have identified self-injurious behavior as an important predictor. of suicidal potential [37,[39][40][41]. This approach provides clues about possible future lines of research, since this study did not explore the motivations for NSSI, which were not necessarily directly related to suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%